SELF-EFFICACY: STAIRCASE TO THE INTENTION OF EMPLOYEES' TURNING-OVER - Johansyah Anwar; R. Madhakomala R. Madhakomala (IJHCM (International Journal of Human Capital Management), 2017)
The aim of this study is to explore and to analyze the impact of self efficacy to employees, mostly considered as those performing ones who have their own certain level of self efficacy, and its effect to turnover intention.Attempting to assess the influence of self efficacy on the intention of individuals to leave the organization, it is observed that individuals having high level of self-efficacy, though reveal in such a positive effect in their cooperation to attain the objectives of the organization, appears to be one among the reasons why they intend to leave the organization and to look for entering a new one.The writer has put his best effort to identify the main implications of self efficacy of employees and following up to increase the level of motivation to more perform in such an efficient and effective manner, and at the same time to minimize employee turnover. It is all for the sake of retaining those employees with high level of self efficacy for the well-being of the organization to achieve its sustainable corporate competitive advantage.Keywords: self efficacy, employee turnover intention.